Crab Spider Lures Prey In Flowerless Neighborhoods - Camila Vieira (Nature Portfolio, 2017)
Abstract One fundamental question in prey luring systems is to understand how visual signals are interpreted by the receiver. Predators lure prey by falsely imitating the signal of a model, or may exploit sensory preferences of the receivers, which search for rewarding signals. Crab spiders reflect ultraviolet (UV) light, ambush pollinators on flowers, and manipulate flower UV signals altering the behavior and response of prey. Whereas crab spiders typically depend on flowers to forage, adult Epicadus heterogaster departs from this standard behavior by preying on pollinators upon green leaves, even in the absence of flowers nearby. This species has a conspicuous abdomen resembling the shape of a flower, which may reflect UV signals similar to that of flowers, and thus attract pollinators. Nevertheless, no empirical evidence is available that E. heterogaster foraging on leaves mimics flowers, nor how this crab spider interacts with its prey. Field and laboratory experiments demonstrated that UV reflection of adult E. heterogaster is the main signal responsible for the attraction of pollinators. This is the first study to demonstrate that a crab spider attracts pollinators regardless of flower UV signal, which may represent an evolutionary pathway beyond the dependence of flowers.